Natural solution to worm problem - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
A natural way to control intestinal worms has been found in Scottish sheep. The discovery opens the way to transfering this natural trait into other breeds at a time when resistance to drugs is making worming of sheep increasingly costly and...